2021
DOI: 10.1128/mra.01407-20
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Burkholderia cenocepacia Phage Mica

Abstract: Burkholderia cenocepacia is a multidrug-resistant Gram-negative pathogen known to colonize patients with chronic granulomatous disease and cystic fibrosis. Here, we describe Burkholderia phage Mica, which is predicted to be a lysogenic myophage based on the similarity of its structural proteins to Enterobacteria phage P2 and Burkholderia phage KL3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…A BLAST search using sequences of Murka’s sequences indicated that Foxunavirus phages were the closest relatives. The search also found related phages infecting bacteria, other than Xanthomonas , including Burkholderia phage Mica (genus Micavirus ) [ 60 ], Achromobacter phage Mano (genus Manovirus ) [ 61 ], Acinetobacter phage Alexa (unclassified), Escherichia phage vB_EcoM-ep3 (genus Jilinvirus ) [ 62 ], and Serratia phage MQ-4 (unclassified) [ 63 ]. The results of comparative genome alignment showed a similarity of genomic organization between these phages, Foxunavirus phages, and phage Murka ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…A BLAST search using sequences of Murka’s sequences indicated that Foxunavirus phages were the closest relatives. The search also found related phages infecting bacteria, other than Xanthomonas , including Burkholderia phage Mica (genus Micavirus ) [ 60 ], Achromobacter phage Mano (genus Manovirus ) [ 61 ], Acinetobacter phage Alexa (unclassified), Escherichia phage vB_EcoM-ep3 (genus Jilinvirus ) [ 62 ], and Serratia phage MQ-4 (unclassified) [ 63 ]. The results of comparative genome alignment showed a similarity of genomic organization between these phages, Foxunavirus phages, and phage Murka ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%